2014
DOI: 10.1071/is13062
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy of Acrapex stem borers (Lepidoptera : Noctuidae : Apameini): combining morphology and Poisson Tree Process analyses

Abstract: Abstract. Ten morphologically similar species of Acrapex from eastern and south-eastern Africa belonging to the A. stygiata and A. albivena groups are reviewed. Six species are described as new: A. brunneella, A. mitiwa, A. mpika, A. salmona, A. sporobola and A. yakoba. The Poaceae host plants of eight species are recorded; four species, A. mitiwa. A. subalbissima, A. syscia and A. yakoba, were found developing exclusively on Imperata cylindrica (L.) Beauv., (Andropogoneae); two species, A. sporobola and A. sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
(42 reference statements)
1
10
0
Order By: Relevance
“…The newly recorded noctuid stem borer species in our study could possibly be endemic to Ethiopia. Similar studies conducted in sub‐Saharan Africa also confirmed the presence of a high rate of endemism in noctuid stem borers particularly in the genus Acrapex (Le Ru, Capdevielle‐Dulac, C., Musyoka, B. K., Goftishu, et al., ; Le Ru, Capdevielle‐Dulac, C., Musyoka, B. K., Pallangyo, B., Njaku, M., Goftishu, et al., ; Le Ru, Capdevielle‐Dulac, C., Musyoka, B. K., Pallangyo, B., Njaku, M., Kandonda, et al., ; Le Ru et al., ). As part of the Eastern Afromontane hotspot, the Ethiopian highlands are known for their high concentrations of endemic species (CEPF, ; Mittermeier et al., ; Williams et al., ).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The newly recorded noctuid stem borer species in our study could possibly be endemic to Ethiopia. Similar studies conducted in sub‐Saharan Africa also confirmed the presence of a high rate of endemism in noctuid stem borers particularly in the genus Acrapex (Le Ru, Capdevielle‐Dulac, C., Musyoka, B. K., Goftishu, et al., ; Le Ru, Capdevielle‐Dulac, C., Musyoka, B. K., Pallangyo, B., Njaku, M., Goftishu, et al., ; Le Ru, Capdevielle‐Dulac, C., Musyoka, B. K., Pallangyo, B., Njaku, M., Kandonda, et al., ; Le Ru et al., ). As part of the Eastern Afromontane hotspot, the Ethiopian highlands are known for their high concentrations of endemic species (CEPF, ; Mittermeier et al., ; Williams et al., ).…”
Section: Discussionsupporting
confidence: 57%
“…The occurrence of rare species in the natural habitat was frequently reported for herbivorous insects in tropical regions (Le Ru, Ong'amo, Moyal, Muchugu, et al., ; Novotny & Basset, ; Ong'amo et al., ). The presence of rare species may not necessarily indicate sampling artifacts, as in the face of very intensive sampling, the incidence of rare species are also common (Le Ru et al., ; Moyal et al., ). The newly recorded noctuid stem borer species in our study could possibly be endemic to Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 185 adults from this species group were collected in light traps set up in Cameroon, Kenya, the Republic of the Congo, Tanzania, Uganda and Zambia. The morphological study is based on 72 adult specimens belonging to 10 Acrapex species collected in 46 localities in seven countries: Cameroon, the Democratic Republic of the Congo, Kenya, the Republic of the Congo, Tanzania, Uganda and Zambia (see also Le Ru et al 2014). Plant specimens were identified by Simon Mathenge (Botany Department, University of Nairobi, Kenya).…”
Section: Samplingmentioning
confidence: 99%
“…We also included one representative of the A. stygiata species group (A. stygiata) and five representatives of the A. albivena species group (A. albivena Hampson, 1910, A. salmona Le Ru, 2014, A. sporobola Le Ru, 2014, A. syscia Fletcher, 1961and A. yakoba Le Ru, 2014. As outgroups, we included representatives of four other genera in the subtribe Sesamiina based on the results of several molecular studies (Toussaint et al 2012;Le Ru et al 2014). DNA was extracted from hind legs using Qiagen DNAeasy tissue kits (Qiagen, Hilden, Germany).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation